Eating Attitudes, Menstruation Cycles and Physical Profiles of Turkish Female Elite Artistic Gymnasts - Pinar Tatlibal, (Pakistan Journal of Medical & Health Sciences, 2022)
It is thought that female artistic gymnasts (AG) who do long-term and high-intensity exercise and whose body fat percentage should be low may have disorders in their eating attitudes and menstruation cycles. These problems can lead to poor performance and, more importantly, undesirable health problems in the future. Therefore, the aim of this study is to examine the eating attitudes, menstrual cycles and physical profiles of female elite AG who train for long periods and at high intensity. Thirteen elite female AG participated in this study (Turkey National Team gymnasts). The height of all participants was measured with an ultrasonic height meter (Langen Messstab 5003, Germany). Body weight, body mass index (BMI), body fat percentage, total muscle mass, bone mineral weight, basal metabolic rate and body fluid ratios were determined by body composition monitor (Tanita BC 401, Japan). Eating attitudes of the participants were determined with the Eating Attitudes Test (EAT-26). With the Menstrual Cycle Form, the participants' menstrual cycles, pain conditions during menstruation, whether they had a gynecological operation, whether they gave birth or not, and the use of oral contraceptive pills were obtained. Training histories and temporal training intensities were determined with the Training Information Form. The EAT-26 Test results, which were within the normal range in the results of this study, were not different in gymnasts with and without menarche (p<0.05). However, the fact that 46.2% (6 gymnasts) of the elite female AG with a mean age of 18.31 ± 4.54 years did not start menarche, suggesting primary amenorrhea in these athletes.